THE EFFECTIVE WAYS OF TEACHING SPEAKING TO YOUNG LEARNERS USING IDIOMS - Sidikova.N.N; Isroilova Zulfiya Sirojiddinovna; Karomiddinova Sitorabonu Kamoliddin qizi (TADQIQOTLAR, 2026)
This article explores effective strategies for teaching speaking skills to young learners through the use of idioms. It emphasizes the significance of idioms in enhancing language fluency and cultural understanding. The article outlines various pedagogical approaches, including contextual learning, visual aids, role-playing activities, and interactive games, to engage students and facilitate their understanding of idiomatic expressions. Furthermore, it discusses assessment methods to track progress and encourage the continued use of idioms in everyday conversation. By integrating idioms into language instruction, educators can foster a more authentic and expressive use of language among young learners.